Fflur - Jones, Lloyd (Y Lolfa, 2019)
A prequel to Dŵr, this romantic love story, interwoven with elements of the supernatural is set in rural Wales. We follow Eirlys, a maid on Dolfrwynog farm who records everything about her life in the close community of Cwm y Blodau between the two world wars.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books